Engineering of TM1459 from Thermotoga maritima for Increased Oxidative Alkene Cleavage Activity - Fink, Matthias; Trunk, Sarah; Hall, Mélanie; Schwab, Helmut; Steiner, Kerstin (Frontiers in Microbiology, 2016)
Oxidative cleavage of alkenes is a widely employed process allowing oxyfunctionalization to corresponding carbonyl compounds. Recently, a novel biocatalytic oxidative alkene cleavage activity on styrene derivatives was identified in TM1459 from Thermotoga maritima. In this work we engineered the enzyme by site-saturation mutagenesis of active site amino acids to increase its activity and to broaden its substrate scope. A high-throughput assay for the detection of the ketone products was successfully developed. Several variants with up to two fold improved conversion level of styrene derivatives were successfully identified. Especially changes in or removal of the C-terminus of TM1459 increased the activity most significantly. These best variants also displayed a slightly enlarged substrate scope.